Some Twentieth-Century Canadian Earthquakes - Stevens, Anne (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1977)
Summary Six contemporary earthquakes have been chosen to illustrate typical effects of past earthquakes in southern Canada - 1925,1929,1944,1973 in eastern Canada; 1909 in central Canada; 1946 in western Canada. In the epicentral region brick chimneys of frame houses have broken at the roof line or have lost bricks from the top. Damage has been greater in structures not located on rocky ground or not well designed, constructed or maintained. Twenty-eight persons drowned following two earthquakes. The effects of future earthquakes may differ in nature and extent from those experienced in the past, particularly if such events are centred near urban areas.